Antecedents And Consequences Of Using Artificial Intelligence (Ai) Color Cosmetics - Sihaloho, Martua Parningotan; Kurniawati, Kurniawati; Masnita, Yolanda (International Journal Labs, 2023)
Sales growth of consumer goods industry especially on cosmetics segment have decreased due to pandemic Covid 19. One of source growth can be attributed to the integration of advanced technologies such as Artificial Intelligence (AI). The purpose of this research is to analyze antecedents and consequences of using artificial Intelligence (AI) Color Cosmetics. Hence, an online survey was conducted to 180 respondents with a series of questions to assess research variables. Data analyses were administrated in two phases, which are Confirmatory Factor Analysis (CFA) and Structural Equation Modelling. The results show that AI Color Cosmetic application utilization can be enhanced by optimizing price sensitivity, social media addiction, and perceived usefulness. These variables play a crucial role in encouraging users to utilize the AI Color Cosmetic application. After using AI Color Cosmetics, there is a significant likelihood that prospective clients will make Actual Purchases. This research found numerous managerial ramifications, particularly for the cosmetics sector's Marketing and Business Development division. The two divisions must consider the Price Sensitivity and Perceived Usefulness elements that prospective clients feel.